Producing Cyclopropane Fatty Acid in Plant Leafy Biomass via Expression of Bacterial and Plant Cyclopropane Fatty Acid Synthases - Okada, Shoko; Taylor, Matthew; Zhou, Xue-Rong; Naim, Fatima; Marshall, David; Blanksby, Stephen J.; Singh, Surinder P.; Wood, Craig C. (Frontiers in Plant Science, 2020)
Saturated mid-chain branched fatty acids are widely used in the petrochemical industry for their high oxidative stability and low melting temperature. Dihydrosterculic acid (DHSA) is a cyclopropane fatty acid (CPA) that can be converted to SMCBFA via hydrogenation, and therefore oils rich in DHSA are a potential feedstock for SMCBFA. Recent attempts to produce DHSA in seed oil by recombinant expression of cyclopropane fatty acid synthases (CPFASes) resulted in decreased oil content and poor germination or low DHSA accumulation. Here we explored the potential for plant vegetative tissue to produce DHSA by transiently expressing CPFAS enzymes in leaf. When CPFAS from plant and bacterial origin were transiently expressed in Nicotiana benthamiana leaf, it accumulated up to 1 and 3.7% DHSA in total fatty acid methyl ester (FAME), respectively, which increased up to 4.8 and 11.8%, respectively, when the N. benthamiana endogenous oleoyl desaturase was silenced using RNAi. Bacterial CPFAS expression produced a novel fatty acid with a cyclopropane ring and two carbon-carbon double bonds, which was not seen with plant CPFAS expression. We also observed a small but significant additive effect on DHSA accumulation when both plant and bacterial CPFAS were co-expressed, indicative of activity upon different oleoyl substrates. Lipidomics analyses found that CPFAS expression increased TAG accumulation relative to controls and that DHSA was distributed across a range of lipid species, including diacylglycerol and galactolipids. DHSA and the novel CPA was present in phosphatidylethanolamine when bacterial CPFAS was expressed in leaf. Finally, when plant diacylglycerol acyltransferase was coexpressed with the CPFASes DHSA accumulated up to 15%. This study shows that leaves can readily produce and accumulate DHSA in leaf oil. Our findings are discussed in line with current knowledge in leaf oil production for a possible route to DHSA production in vegetative tissue.